Casein kinase 2 binds and phosphorylates the nucleosome assembly protein-1 (NAP1) in Drosophila melanogaster - Li, Mingfa; Krehan, Andreas; Pyerin, Walter; Heid, Hans; Mechler, Bernard (Journal of molecular biology, 1999)
The nucleosome assembly protein-1 (NAP1) was originally identified in HeLa cells as a factor facilitating the in vitro assembly of nucleosomes. However, in yeast cells NAP1 is required in the control of mitotic events induced by the Clb2/p34CDC28. Here, we show that Drosophila NAP1 is a phosphoprotein that is associated with a kinase able to phosphorylate NAP1. By using an in-gel kinase assay we found that this kinase displays a molecular mass of 38 kDa. Following purification and peptide microsequencing, we identified the kinase phosphorylating NAP1 as the α subunit of casein kinase 2 (CK2). With the help of a series of NAP1 segments and synthetic peptides, we assigned the CK2 phosphorylation sites to residues Ser118, Thr120, and Ser284. Interestingly, Ser118 and Thr120 are located within a PEST domain, while Ser284 is adjacent to the nuclear localization signal. Substitution of the identified phosphoresidues by alanine was found to reduce considerably the ability of CK2 to phosphorylate NAP1. The enhanced ability of CK2 to phosphorylate phosphatase-treated NAP1 extracted from Drosophila embryos and the similar tryptic phospho-peptide pattern of in vivo labelled NAP1 and in vitro labelled NAP1 with CK2 indicate that NAP1 is a natural substrate of CK2. Further analysis revealed that both CK2α and β subunits are associated with NAP1 but we found that only the catalytic α subunit establishes direct contact with NAP1 on two distinct domains of this protein. The location of CK2 phosphorylation sites in NAP1 suggests that their phosphorylation can contribute to a PEST-mediated protein degradation of NAP1 and the translocation of NAP1 between cytoplasm and nucleus.